The legality and morality of judicial retirement ages. Issue 4 (December 2018) - Goosey, Stuart
The judicial retirement age in the United Kingdom, which requires judges to retire before they reach the age of 70, engages the age discrimination provisions of the Equal Treatment Framework Directive [2000/78/EC] and therefore is only lawful if it is shown to be a 'objectively and reasonably justified by a legitimate aim'. This article argues that the judicial retirement age is justified and therefore lawful under European Union law. In support of this argument, I outline a pluralist theory of age discrimination that consists of principles that explain when age-differential treatment wrongs people and when that treatment is justified. The theory includes the following principles: equality of opportunity, social equality, autonomy, respect and efficiency. After considering these principles, I argue that the judicial retirement age in the United Kingdom is justified by advancing equality of opportunity and social equality by increasing the turnover of judges and therefore increasing the number of vacancies for younger people and under-represented groups.